2013
DOI: 10.1016/j.neuro.2013.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of LRRK2 in control and DAT transfected HEK cells increases manganese-induced oxidative stress and cell toxicity

Abstract: The extra-pyramidal symptoms associated with manganism often overlap with that seen in Parkinsonism suggesting a common link between the two disorders. Since wide deviations are observed in susceptibility and characteristics of the symptoms observed in manganism, these differences may be due to underlying genetic variability. Genes linked to early onset of Parkinsonism which includes ATP13A2 and parkin have already been suggested to promote development of Mn toxicity. Of the other Parkinson-linked genes, mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…What is most significant is the observation that Mn stimulates phosphorylation activity of the G2019S mutant protein, whereas it inhibits wild-type kinase activity normally activated by Mg. 151,152 Recent studies have confirmed that when LRRK2 is silenced with an shRNA, Mn can potentiate oxidative stress, leading to cell death as indicated by activation of both ROS and JNK. 153 In contrast, Mn was shown to reduced phosphorylation of p38, consistent with the fact that p38 is a likely a downstream substrate of LRRK2. 154 Unlike the other genes associated with Mn toxicity, LRRK2 is an autosomal dominant gene and therefore potentially differentiates a population of individuals that, upon exposure to excess Mn, can develop early symptoms of manganism even in the absence of overt signs of Parkinson's disease.…”
Section: Lrrk2mentioning
confidence: 56%
“…What is most significant is the observation that Mn stimulates phosphorylation activity of the G2019S mutant protein, whereas it inhibits wild-type kinase activity normally activated by Mg. 151,152 Recent studies have confirmed that when LRRK2 is silenced with an shRNA, Mn can potentiate oxidative stress, leading to cell death as indicated by activation of both ROS and JNK. 153 In contrast, Mn was shown to reduced phosphorylation of p38, consistent with the fact that p38 is a likely a downstream substrate of LRRK2. 154 Unlike the other genes associated with Mn toxicity, LRRK2 is an autosomal dominant gene and therefore potentially differentiates a population of individuals that, upon exposure to excess Mn, can develop early symptoms of manganism even in the absence of overt signs of Parkinson's disease.…”
Section: Lrrk2mentioning
confidence: 56%
“…This effect was induced by the Rb in the MWCNT supernatant. Some metals are known to produce reactive oxygen species (Ding et al, 2008) that can result in oxidative stress on lipids, DNA and proteins (Henriksson and Tjalve, 2000;Choi et al, 2007;Alekseenko et al, 2008;Kim et al, 2011;Latronico et al, 2013;Roth and Eichhorn, 2013;Sripetchwandee et al, 2013). Thus, we examined the involvement of ROS in the suppression of NSC proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, G2019S mutation of LRRK2 enhanced KIN domain-Mn interactions, prolonging and increasing LRRK2 kinase activity [142]. In contradiction to these findings, studies showed that Mn-induced oxidative stress and neurotoxicity are exacerbated after LRRK2 downregulation in HEK293 cells, suggesting a protective role of LRRK2 in Mn toxicity [143]. These findings indicate that Mn toxicity may involve alterations in the kinase activity of LRRK2 and its regulation of the autophagy-lysosomal pathway, warranting further exploration of the gene-environmental interaction in pathogenic PTMs.…”
Section: Lrrk2mentioning
confidence: 99%